Analisis Monitoring dan Review Risiko pada Operasional Depot Isi Ulang Air Galon Barokah - Rahima Dwi Abdullah; Wahyu Hidayat (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study was conducted to address contamination risks in Refill Drinking Water Depot (DAMIU) operations when sanitation, equipment maintenance, and quality control are not consistently implemented. This emphasizes the critical importance of systematic risk monitoring and review processes to ensure water quality and safety. The research aims to analyze the implementation of risk monitoring procedures, identify operational risks at each processing stage, and evaluate the effectiveness of risk mitigation strategies at Depot Isi Ulang Air Galon Barokah. A descriptive qualitative approach was employed, utilizing data collection techniques including in-depth interviews, direct field observations, and documentation analysis. The findings reveal that monitoring and risk review processes are conducted routinely, encompassing raw water quality checks, equipment sanitation protocols, and customer gallon container inspections. No significant risks were identified during the study period, as potential hazards such as microbiological contamination and equipment malfunction were effectively prevented through timely filter replacement and daily equipment cleaning procedures. Overall, the depot's risk management system operates effectively and consistently maintains water quality standards, ensuring product safety for consumers.